PELAKSANAAN PROSEDUR KERJA PRAMUSAJI DI KARANG RESTAURANT KTM RESORT BATAM - Ekasari, Safrida; Yusrizal, Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research aims to determine the implementation of work procedures from several tasks performed by waitresses at the Karang Restaurant KTM Resort Batam, as well as knowing the obstacles in the implementation of tasks, and the efforts that have been made by management in minimizing these obstacles. This research uses qualitative methods to examine the problem under study by making six key informants as resource persons, namely three restaurant captains, two waitresses, and a guest. While data collection techniques in this researche use observation, interviews and documentation. Based on the results of the research that has been carried out, for the whole of the results of the interview answers said that the implementation of work procedures performed by waiters is sufficient to follow the rules that are set and do the job well, but still need improvement to get optimal work results. In the implementation, work procedures that done by waiter/ss starting from before the restaurant open, during operational, and closing procedures, had been done based on the written work procedures that given by the management.Keywords: Implementation, Work Procedures, Waitresses, Restaurant